Evaluating and Improving Relative Efficiency The Banking Sector in Iraq Using Data Envelopment Analysis of The Output-Oriented VRS Model With Application - Hassan Ismeel , Ismeel; Mohammed Naser AlAshari , Omar (Journal of Economics and Administrative Sciences, 2024)
The banking sector is one of the important sectors in Iraq, and the last stage witnessed the emergence of several private banks in the competition market, and in order to determine the efficiency of existing banks, the resources available to government and private banks were analyzed and compared with two international banks to determine their efficiency ratios for the surveyed banks using data envelopment analysis, the research problem was diagnosed in the lack of interest in measuring the efficiency of banks by exploiting the resources available to maximize profits, the aim of the research is to determine the efficiency of the banks studied according to the direction of outputs and to conduct continuous analysis of the results in order to come up with recommendations that contribute to improving the banking sector. The research focused on the direction of increasing outputs with constant inputs in order to maximize returns. The( Deap2.1) data analysis program was used, and the research adopted data for 2022 to measure efficiency. For 22 banks operating in Iraq (governmental and private) and two banks outside iraq, the variable volume returns (VRS) model was used, and the most prominent results achieved were the achievement of banks The following banks (Rasheed, industrial, TBI, Al-Ahli, Asia, National,trans-Iraq, Jordanian capital, Lloyds Banking Group London) achieved high efficiency100% as they used their resources optimally. The investment bank achieved 90.8%, which is a good percentage, with the ability to benefit from the expertise of industrial and national banks, Jordanian capital, and Lubd’s Banking Group London to reach 100% efficiency in 2022.